Rezar e festejar: religiosidade popular e patrimônio cultural no reisado do norte do Piauí e leste maranhense (2009-2024) - Rocha, Maria do Amparo Moura Alencar (Universidade do Vale do Rio dos Sinos, 2025)
The “Santos Reis” or “Reisado” festival that we analyze in this thesis is a redefinition of a ritual that was introduced to Brazil by Portuguese colonists who celebrated the birth of baby Jesus by making reference to the three “Wise Men”. This was a religious event found throughout the Iberian Peninsula, in which it was common to give and receive gifts along with singing and dancing in homes. In the North of Piauí and the East of Maranhão, the festival dedicated to the “Santos Reis”, which begins with the payment of an ex-voto in recognition of a grace received, has become traditional. The festival is composed of several symbolic elements, typical of the Northeast and representative for the celebrants. Among them are specific costumes, prayers and and songs, as well as characters such as the “boi”, the “cavalo vem”, the “burrinha” and the Caretas. In this work, we study celebrations of “Santos Reis” the took place between 2009 and 2024 in cities in the North of Piauí and East of Maranhão, asking how the experience revived in this practice composes the history of people and places. Based on the consultation of a reference historiography on the theme of popular devotions (Brandão, 1980; Zaluar, 1983) and religious festivals dedicated to the Three Kings (Barroso, 1996; 2013; Cornélio, 2009; Menezes, 2018). Our objective is to analyze the diversity of the theatricalization of faith in the celebrations of the Three Kings in these two territories, which illuminates the understanding of aspects still unknown in the historiography about the Reisado. The Three Kings festival is configured as a cultural heritage of the festival-goers, which promotes in the subjects involved, the appreciation of their history and culture, emerging from it rich constructions for the understanding of the diversity of the celebration of the Saints. And also, it contributes to reflections on the relationships between individuals and groups, their practices, giving indications of how social and cultural roles are constructed, consolidating actions, knowledge and doings of religious practices.
Keywords: Reisado; Religiosidade popular; Nordeste brasileiro; Cultura; Patrimônio; Popular religiosity; Northeast Brazil; Culture; Heritage; ACCNPQ::Ciências Humanas::História